2019
DOI: 10.1519/jsc.0000000000003461
|View full text |Cite
|
Sign up to set email alerts
|

Does HMB Enhance Body Composition in Athletes? A Systematic Review and Meta-analysis

Abstract: Holland, BM, Roberts, BM, Krieger, JW, and Schoenfeld, BJ. Does HMB enhance body composition in athletes? A systematic review and meta-analysis. J Strength Cond Res 36(2): 585-592, 2022-The purpose of this article was to systematically review and meta-analyze the current literature to determine the effects of HMB on body composition in athletes. Studies were deemed eligible for inclusion if they met the following criteria: (a) were an experimental design published in a peer-reviewed, English-language journal; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 48 publications
2
15
0
Order By: Relevance
“…This systematic review and meta-analysis showed that HMB ingestion does not augment RET-induced changes in body composition or strength following weeks or RET (7.6 ± 4.0 wk) in adults between the ages of 18 and 45 years old. These findings are in line with results from previous meta-analyses focusing on HMB supplementation [7,11,28]. Nevertheless, a small significant effect was observed for TBM.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…This systematic review and meta-analysis showed that HMB ingestion does not augment RET-induced changes in body composition or strength following weeks or RET (7.6 ± 4.0 wk) in adults between the ages of 18 and 45 years old. These findings are in line with results from previous meta-analyses focusing on HMB supplementation [7,11,28]. Nevertheless, a small significant effect was observed for TBM.…”
Section: Discussionsupporting
confidence: 92%
“…Eleven studies might be considered a small number when drawing final conclusions. However, this analysis is in line with some of the recently published meta-analyses studying HMB [11,28]. In addition, although there was no significant heterogeneity observed in the analysis of strength gains, the variability between RET protocols might be another limiting factor.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations